2021
DOI: 10.1002/eap.2457
|View full text |Cite
|
Sign up to set email alerts
|

Combining DNA metabarcoding and ecological networks to inform conservation biocontrol by small vertebrate predators

Abstract: In multifunctional landscapes, diverse communities of flying vertebrate predators provide vital services of insect pest control. In such landscapes, conservation biocontrol should benefit service‐providing species to enhance the flow, stability and resilience of pest control services supporting the production of food and fiber. However, this would require identifying key service providers, which may be challenging when multiple predators interact with multiple pests. Here we provide a framework to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 79 publications
0
24
1
Order By: Relevance
“…As the library preparation procedures for Illumina‐based sequencing and MinION‐based sequencing are substantially different, we did not attempt to standardise the steps across platforms. Rather, we compared a MinION protocol that appeared to be working well in our laboratory at CIBIO‐InBIO (Portugal) with an Illumina protocol that has been used in numerous studies (Egeter et al, 2018; Martins et al, 2021; Mata et al, 2021; Peixoto et al, 2021). Initial PCRs to be sequenced with a MinION were performed with a final volume of 25 µl, containing 12.5 µl of Qiagen Multiplex PCR Master Mix (Qiagen, Germany), 0.75 µl of each primer (10 µM), 9.5 µl of ddH 2 O and 1.5 µl of eDNA on a T100 Thermal Cycler (BioRad, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the library preparation procedures for Illumina‐based sequencing and MinION‐based sequencing are substantially different, we did not attempt to standardise the steps across platforms. Rather, we compared a MinION protocol that appeared to be working well in our laboratory at CIBIO‐InBIO (Portugal) with an Illumina protocol that has been used in numerous studies (Egeter et al, 2018; Martins et al, 2021; Mata et al, 2021; Peixoto et al, 2021). Initial PCRs to be sequenced with a MinION were performed with a final volume of 25 µl, containing 12.5 µl of Qiagen Multiplex PCR Master Mix (Qiagen, Germany), 0.75 µl of each primer (10 µM), 9.5 µl of ddH 2 O and 1.5 µl of eDNA on a T100 Thermal Cycler (BioRad, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Rather, we compared a MinION protocol that appeared to be working well in our laboratory at CIBIO-InBIO (Portugal) with an Illumina protocol that has been used in numerous studies (Egeter et al, 2018;Martins et al, 2021;Mata et al, 2021;Peixoto et al, 2021).…”
Section: Pcr Amplification Library Preparation and Sequencingmentioning
confidence: 99%
“…Mata et al. (2021) highlighted the conservation biocontrol potential of bats in a Mediterranean landscape by reference to network structure and interaction frequencies. The study concluded that network ecology and metabarcoding provided a synergistic framework in which both individuals and communities can be assessed effectively in a biocontrol context.…”
Section: Examples Of Dna Metabarcoding In Networkmentioning
confidence: 99%
“…Dietary metabarcoding is increasingly being applied to network ecology in a limited number of recent examples (Clare et al., 2018; Cuff, Drake, et al., 2021; Hemprich‐Bennett et al., 2021; Mata et al., 2021), but these are often isolated predator–prey interactions. However, dietary metabarcoding does theoretically facilitate the merging of complex multilayer networks including many types of interactions across multiple trophic levels, including interactions within trophic levels (i.e.…”
Section: Examples Of Dna Metabarcoding In Networkmentioning
confidence: 99%
See 1 more Smart Citation